Do Reduced Hospital Mortality Rates Lead to Increased Utilization of Inpatient Emergency Care? A Population‐Based Cohort Study. (14th September 2017) - Laudicella, Mauro; Martin, Stephen; Li Donni, Paolo; Smith, Peter C.
Abstract : Objectives: To measure the impact of the improvement in hospital survival rates on patients' subsequent utilization of unplanned (emergency) admissions. Data Sources/Study Setting: Unplanned admissions occurring in all acute hospitals of the National Health Service in England between 2000 and 2009, including 286, 027 hip fractures, 375, 880 AMI, 387, 761 strokes, and 9, 966, 246 any cause admissions. Study Design: Population‐based retrospective cohort study. Unplanned admissions experienced by patients within 28 days, 1 year, and 2 years of discharge from the index admission are modeled as a function of hospital risk‐adjusted survival rates using patient‐level probit and negative binomial models. Identification is also supported by an instrumental variable approach and placebo test. Principal Findings: The improvement in hospital survival rates that occurred between 2000 and 2009 explains 37.3 percent of the total increment in unplanned admissions observed over the same period. One extra patient surviving increases the expected number of subsequent admissions occurring within 1 year from discharge by 1.9 admissions for every 100 index admissions (0.019 per admission, 95% CI, 0.016–0.022). Similar results in hip fracture (0.006[0.004–0.007]), AMI (0.006[0.04–0.007]), and stroke (0.004(0.003–0.005)). Conclusions: The success of hospitals in improving survival from unplanned admissions can be an important contributory factor to the increase in subsequent admissions.